2019
DOI: 10.1111/bph.14717
|View full text |Cite
|
Sign up to set email alerts
|

Non‐sedating antihistamines block G‐protein‐gated inwardly rectifying K+ channels

Abstract: Background and Purpose A second‐generation antihistamine, terfenadine, is known to induce arrhythmia by blocking hERG channels. In this study, we have shown that terfenadine also inhibits the activity of G‐protein‐gated inwardly rectifying K+ (GIRK) channels, which regulate the excitability of neurons and cardiomyocytes. To clarify the underlying mechanism(s), we examined the effects of several antihistamines on GIRK channels and identified the structural determinant for the inhibition. Experimental Approach E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 69 publications
0
30
0
Order By: Relevance
“…To reveal the location of the novel ion permeation route, we introduced a point mutation into the PH located behind the SF, since there is a pocket accessible from the extracellular side surrounded by the side chains of amino acid residues of the SF and PH in the WT. We previously reported that the S148F mutant located at the center of the PH in Kir3.2 is Na + -permeable (16) (Fig. 6a).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…To reveal the location of the novel ion permeation route, we introduced a point mutation into the PH located behind the SF, since there is a pocket accessible from the extracellular side surrounded by the side chains of amino acid residues of the SF and PH in the WT. We previously reported that the S148F mutant located at the center of the PH in Kir3.2 is Na + -permeable (16) (Fig. 6a).…”
Section: Resultsmentioning
confidence: 93%
“…An ion pair, conserved in the Kir channel family, a glutamic acid located in the pore helix (PH) and an arginine located in the extracellular loop behind the SF, is known to contribute to stabilization of the pore structure and maintaining ion selectivity (Yang, Yu, Jan, & Jan, 1997). Mutations of other residues in the PH, such as Ser148 or Glu152 of mouse Kir3.2, also impair the K + selectivity (Chen et al, 2019; Yi, Lin, Jan, & Jan, 2001). Mutations located in transmembrane domains (TMs) outside the SF also alter ion selectivity and residues located at the central cavity can also influence the ion selectivity through interaction with the permeating ions (Bichet, Grabe, Jan, & Jan, 2006; Bichet et al, 2004; Matamoros & Nichols, 2021; Yi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“… 16 18 Drug inhibition or blockade of ion channels is the most common treatment for heart arrhythmia. 19 , 20 Therefore, changes in action potential waveforms because of alterations in ion currents are useful for understanding drug-induced arrhythmia.…”
Section: Discussionmentioning
confidence: 99%
“…In Dr. Yoshihiro Kubo's lab, studies on the structurefunction relationship of ion channels using an in vitro expression system are performed in order to elucidate their functional mechanisms. In particular, the Kubo lab is interested in the stoichiometry and gating of voltage-gated K + channel complexes, the effects of drugs on G protein-coupled inward rectifier K + channels (Chen et al 2019), the regulation of twopore Na + channel 3 by PIP2 and voltage (Shimomura To elucidate the molecular mechanisms by which TRP channels are either activated or inactivated below or above a particular temperature threshold, the group utilizes a variety of experimental techniques including cell biology, biochemistry, and patch-clamp/calcium imaging . Results obtained with these different approaches are often compared with behavioral analyses of mice lacking thermosensitive TRP channels, thereby permitting the interpretation of experimental results in an integrative manner (Takayama et al 2017).…”
Section: Biophysical Research At the Nipsmentioning
confidence: 99%